Testing for Facioscapulohumeral Muscular Dystrophy using Optical Genome Mapping and Exome Sequencing - Anja Kovanda; Borut Peterlin (Medical Research and Its Applications Vol. 10, 2024)
Background: Facioscapulohumeral muscular dystrophy (FSHD) is the third most common hereditary muscular dystrophy and is inherited in an autosomal dominant manner in case of FSHD1 and as a digenic disorder in case of the rarer FSHD2 form. FSHD is caused in both cases by the inappropriate expression of the DUX4 gene, which in healthy individuals is silenced by the methylation of the neighbouring D4Z4 repeats. With rare exceptions, only the contraction of the D4Z4 repeats on the permissive 4qA haplotype on chromosome 4 causes FSHD1, while FSHD2 is caused by the demethylation of the D4Z4 repeats on the permissive haplotype due to pathogenic variants in the genes regulating the methylation of this region, SMCHD1, DNMT3B and LRIF1. Traditional diagnostics of FSHD is based on Southern blot, a time- and effort-intensive method that can be affected by single nucleotide (SNV), and copy number variants (CNV), as well as by the similarity of the D4Z4 repeats located on chromosome 10. We aimed to perform an independent evaluation of optical genome mapping (OGM) as an alternative molecular diagnostic method for the detection of FSHD. Methods: We first performed optical genome mapping with EnFocus™ FSHD analysis using DLE-1 labeling and the Saphyr instrument, for our patients with inconclusive diagnostic Southern blot results, negative FSHD2 results, and clinically evident FSHD. Secondly, we performed OGM in parallel with the classical Southern blot analysis for our prospectively collected new FSHD cases. Finally, we used panel exome sequencing of relevant genes to confirm or exclude FSHD2. Results: By using OGM we could resolve past cases with diagnostically inconclusive Southern blot results as having shortened D4Z4 repeats on the permissive 4qA allele, consistent with their clinical presentation. Results of the prospectively collected patients tested in parallel using Southern blot and OGM showed full concordance, showing OGM to be a useful alternative to the classical Southern blot method for detecting FSHD1. For a patient showing clinical FSHD but no shortened D4Z4 repeat on the 4qA allele using OGM or Southern blot, we found a likely pathogenic variant in SMCHD1 by using exome sequencing, confirming FSHD2. We suggest OGM and panel exome sequencing can be used consecutively to perform genetic testing in clinical suspected FSHD.